Epidemiological, molecular, and evolutionary characteristics of G1P[8] rotavirus in China on the eve of RotaTeq application - Rui Peng; Rui Peng; Mengxuan Wang; Saleha Shahar; Guangping Xiong; Qing Zhang; Lili Pang; Hong Wang; Xiangyu Kong; Dandi Li; Zhaojun Duan (Frontiers in Cellular and Infection Microbiology)
IntroductionThis study, conducted in China prior to RotaTeq’s launch, examined the epidemiological, molecular, and evolutionary features of the G1P[8] genotype RVA in children admitted with diarrhea, to aid in evaluating its efficacy and impact on G1P[8] RVA in China.MethodsData from the Chinese viral diarrhea surveillance network were collected from January 2016 to December 2018. RVA strains identified as the G1P[8] genotype were subjected to whole-genome sequencing. Neutralizing epitope, amino acid selection pressure, and evolution dynamics analyses on VP7 and VP4 were performed using BioEdit v.7.0.9.0 and PyMOL v.2.5.2, four algorithms (MEME, SLAC, FEL, and FUBAR) in the Datamonkey online software, and the MCMC model in BEAST v. 1.10.4, respectively. Phylogenetic and identity features of 11 genes were assessed by DNAStar and MEGA v.7.ResultsResults showed that the detection rate of G1P[8] in China from 2016 to 2018 was generally low with significant seasonality. The whole genome of G1P[8] of four 2016 childhood diarrhea specimens was successfully sequenced. Phylogenetic and neutralizing epitope analysis showed that Rotavin-M1 might have better protection on G1P[8] prevalent in China than Rotarix and RotaTeq. Two conserved N-glycosylation sites on VP7 of Chinese G1P[8] might affect the protective effect of the vaccine. Evolution rate and selection pressure analysis identified the possibility of rapidly evolving and adapting to the new environment introduced by vaccines of G1P[8], whereas positive selection specific to VP4 indicated the potential tendency to select for dominant traits. Identity and phylogeny analysis showed that Chinese G1P[8] from before 2018 was generally stable with possible genetic recombination among local strains.DiscussionThese findings not only are of great significance for predicting the prevalence of G1P [8] in China, but also provide data reference for evaluating rotavirus vaccine efficacy.